The Global Inequality Boomerang - Ravi Kanbur; Eduardo Ortiz-Juarez; Andy Sumner (Institute of Labor Economics (IZA), 2022)
In this paper we argue that the decline in global inequality over the last decades has spurred a 'sunshine' narrative of falling global inequality that has been rather oversold, in the sense, we argue, it is likely to be temporary. We argue the decline in global inequality will reverse due to changes in the between-country component. We find there is a potentially startling global inequality 'boomerang', possibly in the mid-to-late 2020s, which would have happened even if there were no pandemic, and that the pandemic is likely to bring forward the global inequality boomerang.
Keywords: D31; D63; O15; 330; global inequality; inequality boomerang; COVID-19